Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.34172/ehem.2022.31
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori genes (CagA and VacA) in municipal drinking water

Abstract: Background: Helicobacter pylori is classified as a carcinogen, and it is also the most common cause of chronic bacterial infection and peptic ulcers. Approximately 45% of people are infected with the bacterium. Methods: In this study, the H. pylori genes, CagA and VacA, were investigated in drinking water, using 100 samples (50 samples from the municipal water supply and 50 samples from the effluent of household water treatment devices). DNA was extracted from colonies with a positive heterotrophic plate count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Besides that, Farhadkhani et al [ 11 ] detected H. pylori with a high frequency (36%) in wastewater samples, stressing that fecal pollution of water and other environmental samples plays an important role in H. pylori infection transmission. On the other hand, Gholami-Borujeni et al [ 1 ] reported that 24% of water samples collected from urban areas, and 18% from home water treatment devices in Iran tested positive for H. pylori .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, Farhadkhani et al [ 11 ] detected H. pylori with a high frequency (36%) in wastewater samples, stressing that fecal pollution of water and other environmental samples plays an important role in H. pylori infection transmission. On the other hand, Gholami-Borujeni et al [ 1 ] reported that 24% of water samples collected from urban areas, and 18% from home water treatment devices in Iran tested positive for H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori infection has a significant public health impact on human health in both developed and developing countries, as it is classified by the WHO as a bacterial carcinogen. Additionally, it is commonly associated with chronic infections, and peptic ulcers [1]. Helicobacter pylori is a microaerophilic Gram negative spiral shaped bacteria belonging to the family Helicobacteraceae that particularly colonize the human gastric epithelium and have been isolated from the gastrointestinal tract of many animals, causing one of the most common infections worldwide [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for detecting H. pylori in wastewater, some of which include (7,8) wastewater may be expensive and not feasible for routine monitoring. The detection of vacuolating cytotoxin A (vacA) and cytotoxin-associated gene A (cagA) gens in wastewater can provide valuable information regarding the prevalence of H. pylori in a community.…”
Section: Detection Of Helicobacter Pylori In Water and Wastewatermentioning
confidence: 99%
“…Another challenge is the differentiation between live and dead bacteria in wastewater. Moreover, current detection methods do not distinguish between DNA from live and dead bacteria, which can lead to the overestimation of the prevalence of H. pylori (7). In addition, since the monitoring of Helicobacter in wastewater can provide useful information on the prevalence of the bacteria in a given population, it cannot be used as a definitive measure of the number of infected individuals.…”
Section: Detection Of Helicobacter Pylori In Water and Wastewatermentioning
confidence: 99%